Le traitement macrostructural de l’emprunt au franÃ§ais dans les dictionnaires locaux au Gabon - Ella, Edgard Maillard (Lexikos, 2013)
The Macrostructural Treatment of Borrowings from French in Local Gabonese Dictionaries. Local populations often pragmatically borrow words from other languages, which they need in theirs. This applies mostly when two populations with different languages come in contact as is the case with French and the local languages of Gabon. Borrowing is an unconscious process and an essential factor in the life of all the world’s languages. This is why, although they are less numerous than local words, borrowed words are very common in their vocabularies. Some of these borrowings are replaced by local terms when local populations become familiar with the concepts or things referred to by the foreign words. Some are retained as they are and others are morphophonologically modified in order to adapt to local linguistic characteristics. A dictionary is compiled in accordance with the users. This is why the lexicographer in his turn adopts this pragmatic approach so that the users will identify themselves with the finished work. During the macrostructural treatment when words to include as lemmas are chosen, he initially incorporates borrowings used by the local population. Gradually in revised and corrected editions, he will incorporate local terms which have replaced certain borrowings as well as morphophonological changes undergone by others. In this article, we want to suggest this pragmatic approach to persons who compile dictionaries in Gabon and who are often faced with the absence of many modern words in the local languages. This article goes against lexical creation which is known as being a purist approach and which often proves to be laboured and dubious. We want to show that a pragmatic approach, which incorporates both approaches establishes a methodology, which presents more advantages than a purist approach. The dialect Fang Ntumu of Bitam is used here as an example to support this article, which is suitable for all the other local languages of Gabon.